Osteopathic Approach to Anxiety - Blumer, DO, Tim; Blumer, DO, FAAO, Janice (Osteopathic Family Physician, 2017)
Anxiety disorders are one of the most common psychiatric disorders presenting to the family physician. Anxiety disorders are both biologic and psychologic in origin. Anxiety is a signal alerting the individual of ‘danger.’ This danger can be unknown, internal, conflictual and vague. The anxiety signal allows the individual to respond to, and resolve the ‘danger.’ This is to be differentiated from fear which is the emotional response to a real or perceived imminent threat. These two states overlap but differ in that fear more often triggers the physiologic response of fight or flight. Anxiety disorders result when one or both of these systems are in a chronic ‘hyper reactive’ state for either biologic or psychologic reasons. This article reviews the criteria for anxiety disorders and the range of therapeutic interventions, pharmacologic and non-pharmacologic.